PERLINDUNGAN HUKUM TERHADAP KONSUMEN PERUMAHAN REAL ESTATE BERBASIS BROSUR - Suharmiko, Anton (Magister Ilmu Hukum Sekolah Pascasarjana Unida, 2016)
Housing developer of royal tajur offer many types and kinds of home, the developer began to make an offer-based marketing brochure. In the field of consumers when transactions are received many shortcomings such as in the brochure. The deficiencies include housing incompatibility with what is shown in the brochure. It is very necessary to make the protection of both the law and to the consumer that is based brochure. Identification of this research include of Â implementation of housing purchase agreement between developer and consumer brochures based, disputes between consumers and developers, and settlement of disputes between consumers and developers. The method used in this research is normative juridical approach, the law conceived as norms, rules, principles or dogmas/jurisprudence. Results of this research are: 1) In the execution of a purchase agreement between the developer housing with consumer-based brochures, developers enforce standard contract (standard contract) in any binding agreement buying and selling homes; 2) The occurrence of disputes between consumers and developers, which is the responsibility of the developers when consumers are harmed in a binding sale and purchase agreement; 3) Settlement of disputes between consumers and developers, namely consumer attitudes toward default action/omission of the developer resulting in losses for the consumer to make a complaint to the competent institutions in the protection of consumers, namely BPSK still very minimal.